2014
DOI: 10.5455/bcp.20140131023259
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Lifetime Tobacco, Alcohol and Drug Use Among 10th Grade Students in Istanbul

Abstract: İstanbul'da 10. sınıf öğrencileri arasında yaşam boyu tütün, alkol ve madde kullanım yaygınlığı Amaç: Bu çalışmanın amacı İstanbul/Türkiye'de 10. sınıf öğrencileri arasında yaşam boyu tütün, alkol ve madde kullanma yaygınlığını belirlemektir. Yöntem: İstanbul'un 15 farklı ilçesinde 45 okulda kesitsel yapılan online kendi-bildirimli anket çalışmasıdır. Soru formu demografik verileri, ailede ya da çevrede madde kullanımı, okul yaşamı, sosyal iletişim ve tütün, nargile, alkol, esrar, uçucular, eroin, kokain, reçe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 22 publications
3
22
0
4
Order By: Relevance
“…A higher level of education in the family (Özyurt & Dinç, 2006) and a lower level of education for the mother (İnandı et al, 2009) were both found to be related to drinking. Alcohol use in the family was found to be the lowest (8.3%) in a study from Istanbul (Evren et al, 2014). In another study, the risk of alcohol use was found to be doubled if there was use in the family (Şaşmaz et al, 2006).…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…A higher level of education in the family (Özyurt & Dinç, 2006) and a lower level of education for the mother (İnandı et al, 2009) were both found to be related to drinking. Alcohol use in the family was found to be the lowest (8.3%) in a study from Istanbul (Evren et al, 2014). In another study, the risk of alcohol use was found to be doubled if there was use in the family (Şaşmaz et al, 2006).…”
Section: Resultsmentioning
confidence: 95%
“…Similarly, both high and low income levels were found to be associated with alcohol use (Evren et al, 2014;Ögel et al, 2004;Ögel et al, 2006;Özyurt & Dinç, 2006;Pumeriega et al, 2014).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The aim of the main study conducted through this website was to determine the prevalence of smoking, alcohol use, and substance use among 10 th grade students in Istanbul Turkey, and to compare them with previous studies (41). Data of this previous study were used to conduct the present study.…”
Section: Methodsmentioning
confidence: 99%